POLA KONSUMSI PANGAN NON KARBOHIDRAT PADA PROVINSI TAHAN DAN RAWAN PANGAN (PROVINSI KALIMANTAN TIMUR DAN NUSA TENGGARA TIMUR) TAHUN 2017 - Saputra, Muhamad Ferdian; Firdaus, Muhammad Firdaus; Novianti, Tanti Novianti (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
The problem of national food security could not be resolved if the problems at the lowest level (household) did not resolved. One of the effective strategy to achieve food security was increasing food diversification. This study compared the patterns of consumption and the level of diversification of household food among provinces that were resistant to food insecurity. This study used National Socio-Economic Survey (Survei Sosial Ekonomi Nasional/SUSENAS) data from Statistic Indonesia and analyzed using the Berry index and the Almost Ideal Demand System (LA / AIDS) model. This study found that the level of income and the level of food diversification in food secure province (East Kalimantan) were higher than those in food insecure province (East Nusa Tenggara). The patterns of household food consumption in East Nusa Tenggara province was more influenced by changes in income, while East Kalimantan was subject to price changes.